Migrant worker mental health in Southeast Asia: a bibliometric analysis of public health research (2005–2025) - Suamuang Ruangrit (Intelektual Pustaka Media Utama, 2026)
Southeast Asia hosts an estimated 10-14 million intraregional labor migrants who face disproportionate mental health burdens. No bibliometric study has systematically mapped the intellectual landscape or knowledge gaps of migrant worker mental health research specific to this region. A bibliometric analysis was conducted on peer-reviewed literature indexed in Web of Science and Scopus (January 2005-December 2025), following the BIBLIO checklist. VOSviewer and Bibliometrix (R v4.4) were used for keyword co-occurrence network mapping and publication trend analysis, respectively. A total of 487 eligible records were identified. Annual output grew from fewer than 10 publications per year before 2010 to over 60 per year from 2021 onward. Thailand dominated as the primary study setting (38.6%) and top-producing country (31.4%). Five thematic clusters emerged: i) depression and anxiety screening, ii) occupational stressors, iii) acculturation and social support, iv) healthcare access barriers, and v) social determinants of health. Symptom-prevalence research declined from 68% to 31% while equity-focused research grew from <1% to 14% over two decades. The field has grown substantially but remains geographically concentrated. Equity-focused, structurally informed research agendas are urgently needed to reduce mental health disparities among the region's most vulnerable workers.